The Greenland shark genome: Insights into lifespan extremes and population dynamics - Kaiqiao Yang; Kazuya Nishiwaki; Hideaki Mizobata; Jiancheng Liang; Shuichi Asakawa; Kazutoshi Yoshitake; Yuuki Y. Watanabe; Nigel E. Hussey; Kit M. Kovacs; Christian Lydersen; Mitsutaka Kadota; Shigehiro Kuraku; et al. (Proceedings of the National Academy of Sciences, 2026)
The Greenland shark ( Somniosus microcephalus ) is known for its slow metabolism and deep-sea habitat. It is thought to be the longest-lived vertebrate on Earth, with an estimated lifespan of 392 ± 120 y. Despite its remarkable longevity and unusual lifestyle, no genomic studies are yet available for this species. Here, we report a chromosome-level assembly of the Greenland shark genome, which is 5.9 Gb in size with an N50 length of 233 Mb and a completeness score of 96.7%. Our analyses of gene family expansion and positive selection revealed classical longevity-related mechanisms, including immune enhancement, cancer resistance, and DNA repair, as well as additional features potentially associated with extended lifespan limits. Unique amino acid substitutions in the globular domain of linker histone H1.0 are predicted to enhance chromatin stability, and the species’ distinctive gene repertoire provides a framework for generating hypotheses potentially linking ferroptosis to exceptional longevity. We also elucidate the dynamics of the effective population size ( N e ) of the Greenland shark and its close relative, the Pacific sleeper shark ( Somniosus pacificus ). These genomic analyses offer insights into the molecular basis of the exceptional longevity of the Greenland shark and highlight potential genetic mechanisms that could inform future research into longevity.